3. PERAN MODAL SOSIAL DAN MODAL POLITIK DALAM IMPLEMENTASI KEBIJAKAN PENANGANAN BANJIR DAN ROB (Studi Kasus di Kelurahan Tanjung Mas Kecamatan Semarang Utara Kota Semarang) - Edi Santosa (JIIP: Jurnal Ilmiah Ilmu Pemerintahan, 2015)
Policy on flood and tide management has become a severe public issue. In particular, the issue is dealing with the policy implementation as a manifestation of public service to protecting community as an impact of the flood disaster, which has been a long-standing serious issue. This research, Social and Political Capitals For Implementing Policies on Flood and Tide Management, raises a case study in Tanjung Mas Village, Semarang Utara District, Semarang Municipality. The analysis focuses on research question of whether the potentials social and political capitals contributed a significant role in the implementation of the policy of the Semarang Municipal Government in the flood management. The analysis used an approach of naturalistic (descriptive-qualitative) method with an incidental random sampling data collection and Focus Group Discussion. Respondents were selected purposively with the major component of community leaders and citizens of RW 3-9 who became the victims of the flood. The study results raised some issues and problems concerning the implementation of the policy, which theoretically did not comply with the concept of the policy implementation, in which the policy performers did not optimally accommodate local social and political capitals. The most highlighted finding was that all respondents reported that the policy performers and politicians from the Local Boards of Representatives did not truly implemented the policy, tending to sway from their initial promises during the majoral election campaign of 2009. In their political contracts, one of the legislative candidates from particular party promised that the people of Tanjungmas would be set free from flood, elevated from poverty, and survived from unemployment. In practice, none of these promises were answered. For example, the potential of the social capital (collective work, fundraising, and environmental improvement) and political capital (citizen’s political aspiration and rights) accummulated in vary local and pure associations only had a very minor involvement in solving problems related to flood and tide in Tanjungmas area, development of River Semarang, and infrastructure development – in which Sagorake (Saluran Gorong Gorong Rakyat Kebonharjo) Group was involved. It is important to note that the social capital of the local community may grow by P2KP program introduced by central government through The Ministry of Public Work Affairs. The policy of Semarang Municipal Government did not allow the local people social, political, and economic access to the policy implementation. All the programs of the flood and tide management always took place with a project approach without involving local community. Borrowing the concept introduced by Van Meter and Horn (1975:23), the poor coordination, communication and the successful policy implementation program are crucial in the favor of bureaucrats instead of planning and policy-making processes. What Van Meter and Horn writes was proven by the implementation of the flood and tide management in Semarang. The development of Sistem Polder Tawang Kota Lama as flood and tide controller, tourist and conservation site was useless because of lacking management. In addition to this deficiency, the location had a poor drainage system and became the waste dumping site. According to the findings, this research recommended a change in model of policy on flood and tide management from structural to non-structural paradigm, which accommodates the potential of the social and political capitals as the end target of the policy stakeholder.